Characterization of X-ray beams by Attenuation Method for Calibration of Personal Dosimeters - Benavente, T. (1999)
The choice of the attenuation method to characterize the X rays beams used in the calibration of personal dosemeters at the Calibraion and Dosimetry laboratiry of the Peruvian Institute of Nuclear Energy (IPEN). Voltages applied to the X ray tube and the addition of filters have been made according to the publication ANSI No.13. Half value layer, homogeneity coefficient were found with respect to values published in ANSI No.13. Also spectral distributions and their resolutions were determined. Relative differences of 16 and 9% respectively were found in comparison with values calculated by the Montecarlo's Method.